Asymmetric response of the Atlantic Meridional Ocean Circulation to freshwater anomalies in a strongly-eddying global ocean model. Issue 1 (1st January 2017) - Brunnabend, Sandra-Esther; Dijkstra, Henk A.
Abstract : The Atlantic Meridional Overturning Circulation (AMOC) responds sensitively to density changes in regions of deepwater formation. In this paper, we investigate the nonlinear response of the AMOC to large amplitude freshwater changes around Greenland using a strongly-eddying global ocean model. Due to a 0.5 Sv freshwater input, the maximum AMOC at 35 N decreases by about 50% over a 45 year period. The AMOC does not recover over a period of 50 years when the freshwater input is ceased at year 45. However, when reversing the sign of the freshwater input at year 45, the AMOC needs only about 10 years to fully recover. The mechanism that causes this asymmetric response in the AMOC is clarified using water mass transformation theory.